The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1146/annurev.nutr.24.121803.063211
|View full text |Cite
|
Sign up to set email alerts
|

Structure, Function, and Dietary Regulation of Δ6, Δ5, and Δ9 Desaturases

Abstract: Fatty acid desaturases introduce a double bond in a specific position of long-chain fatty acids, and are conserved across kingdoms. Degree of unsaturation of fatty acids affects physical properties of membrane phospholipids and stored triglycerides. In addition, metabolites of polyunsaturated fatty acids are used as signaling molecules in many organisms. Three desaturases, Delta9, Delta6, and Delta5, are present in humans. Delta-9 catalyzes synthesis of monounsaturated fatty acids. Oleic acid, a main product o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

23
743
3
16

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 934 publications
(803 citation statements)
references
References 201 publications
23
743
3
16
Order By: Relevance
“…3,4,14,19,25,26 A similar pattern was observed in obese children in our study and others, 16,27 although study results have been inconsistent. 18 Desaturase activity Consistent with most previous studies of adults 4,11,14,28 and children, 16,18 we found that the estimated activities of D6 and D9 DAs were positively associated with adiposity and insulin measures in our study of adolescents. Further, D6 DA was also adversely associated with other CVD risk factors, including triglycerides, total cholesterol, LDL-and HDLcholesterol.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…3,4,14,19,25,26 A similar pattern was observed in obese children in our study and others, 16,27 although study results have been inconsistent. 18 Desaturase activity Consistent with most previous studies of adults 4,11,14,28 and children, 16,18 we found that the estimated activities of D6 and D9 DAs were positively associated with adiposity and insulin measures in our study of adolescents. Further, D6 DA was also adversely associated with other CVD risk factors, including triglycerides, total cholesterol, LDL-and HDLcholesterol.…”
Section: Discussionsupporting
confidence: 91%
“…9,10 The composition of fatty acids in the body reflects dietary fat intake and endogenous fatty acid metabolism. 11 Plasma or serum fatty acid composition partly reflects dietary fat intake during the past 2-6 weeks and the fatty acids in body fat tissue represents diet in the past several months or years. 12 Desaturase enzyme activity (modulating fatty acid degree of saturation) 11,13 includes delta (D) 9, D6, and D5 desaturase activities (DAs), the rate-limiting steps for transforming shorter chain fatty acids into longer essential fatty acid metabolites.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The FADS gene cluster encodes the enzymes D 5 and D 6 desaturase (Marquardt et al 2000;Nakamura and Nara 2004), which are involved in the endogenous synthesis of n-3 LCPUFA (Burdge and Calder 2005). PPARG2 and COX2 encode proteins that play a role in the proposed mechanisms behind the effects of n-3 LCPUFA.…”
Section: Introductionmentioning
confidence: 99%
“…Stearoyl-CoA desaturase (SCD) is the key Δ 9 -desaturase in man. The activities of these enzymes produce fatty acids with a greater degree of desaturation, which are required for the efficient synthesis of more complex lipids, such as triacylglycerols [2]. Both animal and human studies suggest that fatty acid desaturases play a role in various metabolic disturbances, such as insulin resistance and dyslipidaemia [3][4][5].…”
Section: Introductionmentioning
confidence: 99%